Correction of the Crooked Nose - Newberry, C. Ian; Mobley, Steven (Facial Plastic Surgery, 2018)
Successful management of the crooked nose can be a formidable task and requires a systematic approach that begins with an understanding of the patients' aesthetic desires, expectations, and functional symptoms. Dividing the nose into thirds and organizing a plan to correct each region individually can simplify the preoperative planning. There are two broad philosophical strategies of surgical management: engineering (reconstructive) and artistic (camouflaging). While the camouflaging technique is helpful for minor asymmetries, protrusions, and depressions, the engineering approach is best for more extreme corrections. The surgeon must be skilled in both approaches as either one or a combination of the two may yield the best results. Once corrected, postoperative care is essential to obtain optimal outcomes.
Keywords: crooked nose; deviated nose; rhinoplasty; spreader grafts; septoplasty